+0  
 
0
667
4
avatar+297 

If we use (x+) to indicate the following sum
   1 + 2 + 3 + ... + x
then find the value of k in the following equation
(28+) - (27+) = (k+)

 Aug 12, 2015

Best Answer 

 #4
avatar+96040 
+10

The sum of the first "k" positive integers is given by :   (k)(k + 1)/2

 

So  (x +)   where x =  28  is just  (28)(29) /2     and  (x+) where x = 27  is just (27)(28)/2 

 

So we have

 

(28)(29)/2 -  (270(28)/2        ..... factor out 28/2

 

[28/2] [ 29 - 27]=

 

[14] [2]  = 28

 

And notice that :

 

1 + 2 + 3 + 4 + 5 + 6 + 7  = 28   

 

So this equals the sum of the first seven positive integers  =  (7)(8)/2  = 56/2 = (7+)

 

 

 

  

 Aug 12, 2015
 #1
avatar+96040 
+5

(28+) - (27+) =

 

(28)(29)/ 2 - (27)(28)/2  =

 

(28) [ (29) - (27) ] / 2 =

 

(28/2) (2) = 28  =  (7)(8)/ 2 =   (7+)   ...so k = 7

 

 

  

 Aug 12, 2015
 #2
avatar+297 
0

I AN NOT GETTING WHAT YOU HAVE GIVEN PLEASE EXPLAIN YOUR ANS TO ME MORE BRIEFLY

 Aug 12, 2015
 #3
avatar+21244 
+10

If we use (x+) to indicate the following sum
   1 + 2 + 3 + ... + x
then find the value of k in the following equation
(28+) - (27+) = (k+)

 

$$\small{\text{$
\begin{array}{rcl}
(28+)-(27+) = (k+) = 28 &=& S_k \qquad (28+) = S_{28} \quad (27+)=S_{27}\\\\
S_{28}-S_{27} = t_{28} = 28&=&S_k\\\\
S_k &=& t_1 \cdot \dbinom{k}{1} + d\cdot \dbinom{k}{2} \qquad t_1=d=1\\\\
S_k &=& \dbinom{k}{1} + \dbinom{k}{2} = \dbinom{k+1}{2} = 28\\\\ \\
\dfrac{k(k+1)}{2} &=& 28 \\\\
k(k+1) &=& 56\\\\
k^2+k-56&=&0\\\\
\Rightarrow k &=& \dfrac{-1+15}{2} = 7\\\\
\mathbf{S_k = (k+) }& \mathbf{=} & \mathbf{(7+)}\\\\
(7+)=1+2+3+4+5+6+7&=&28 \\
\end{array}
$}}$$

 

 Aug 12, 2015
 #4
avatar+96040 
+10
Best Answer

The sum of the first "k" positive integers is given by :   (k)(k + 1)/2

 

So  (x +)   where x =  28  is just  (28)(29) /2     and  (x+) where x = 27  is just (27)(28)/2 

 

So we have

 

(28)(29)/2 -  (270(28)/2        ..... factor out 28/2

 

[28/2] [ 29 - 27]=

 

[14] [2]  = 28

 

And notice that :

 

1 + 2 + 3 + 4 + 5 + 6 + 7  = 28   

 

So this equals the sum of the first seven positive integers  =  (7)(8)/2  = 56/2 = (7+)

 

 

 

  

CPhill Aug 12, 2015

33 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.